Oxygen metabolism analysis of a single organoid for non-invasive discrimination of cancer subpopulations with different growth capabilities - Nashimoto, Yuji; Shishido, Shotaro; Onuma, Kunishige; Ino, Kosuke; Inoue, Masahiro; Shiku, Hitoshi (Frontiers in Bioengineering and Biotechnology, 2023)
Heterogeneous nature is a pivotal aspect of cancer, rendering treatment problematic and frequently resulting in recurrence. Therefore, advanced techniques for identifying subpopulations of a tumour in an intact state are essential to develop novel screening platforms that can reveal differences in treatment response among subpopulations. Herein, we conducted a non-invasive analysis of oxygen metabolism on multiple subpopulations of patient-derived organoids, examining its potential utility for non-destructive identification of subpopulations. We utilised scanning electrochemical microscopy (SECM) for non-invasive analysis of oxygen metabolism. As models of tumours with heterogeneous subpopulations, we used patient-derived cancer organoids with a distinct growth potential established using the cancer tissue-originated spheroid methodology. Scanning electrochemical microscopy measurements enabled the analysis of the oxygen consumption rate (OCR) for individual organoids as small as 100 µm in diameter and could detect the heterogeneity amongst studied subpopulations, which was not observed in conventional colorectal cancer cell lines. Furthermore, our oxygen metabolism analysis of pre-isolated subpopulations with a slow growth potential revealed that oxygen consumption rate may reflect differences in the growth rate of organoids. Although the proposed technique currently lacks single-cell level sensitivity, the variability of oxygen metabolism across tumour subpopulations is expected to serve as an important indicator for the discrimination of tumour subpopulations and construction of novel drug screening platforms in the future.